2017
DOI: 10.1111/pace.13232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety and performance of a MRI conditional pacing system in patients undergoing cardiac MRI

Abstract: cMRI scanning with 1.5 T scanners is safe in patients implanted with the Accent MRI™ conditional pacing system and has no significant effect on the electrical parameters of the device and leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Regarding the position, CMR is particularly susceptible to CIED artifacts because it is positioned near the heart, and the closer the generator is to the apex of the left ventricle, the greater the artifacts. Additionally, the stronger the magnetic field, the greater the artifacts [50,51].…”
Section: Issue: Artifactmentioning
confidence: 99%
“…Regarding the position, CMR is particularly susceptible to CIED artifacts because it is positioned near the heart, and the closer the generator is to the apex of the left ventricle, the greater the artifacts. Additionally, the stronger the magnetic field, the greater the artifacts [50,51].…”
Section: Issue: Artifactmentioning
confidence: 99%
“…In prospective studies of MRI performance in patients with conditional devices scanned at 1.5 T, no changes in pacing or sensing thresholds were observed. [20][21][22][23] There is currently no published, externally validated data for the scanning of MRIconditional pacemakers or defibrillators at 3 T. However, several CIEDs have been certified as conditional at 3 T according to manufacturer testing.…”
Section: Mri For Conditional Devicesmentioning
confidence: 99%
“…16 In a 2017 prospective multicenter randomized controlled trial, which included 283 patients with MR conditional dualchamber PMs, a clinical evaluation and device interrogation for each patient 1 month before and after MRI showed no complication. 17 As for ICDs, a 2015 prospective randomized controlled trial, where 263 patients with MR conditional ICDs underwent full-body MRI, reported only mild MRI-related events in patients. 18 Of these, there were 2 implant site warmth sensations, 1 back pain, 1 forehead burning sensation, and 1 atrial tachycardia associated with asynchronous pacing that was converted by the ICD's antitachycardia pacing.…”
Section: Evidence With Mr Conditional Devicesmentioning
confidence: 99%